2022
DOI: 10.1002/ags3.12616
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on colorectal cancer surgery in Japan: Clinical Study Group of Osaka University―A multicenter retrospective study

Abstract: Aim Due to the overwhelming spread of SARS‐CoV‐2 and its disruption of the healthcare system, delays and reduced numbers were reported for colorectal cancer screening, colonoscopies, and surgery during the COVID‐19 pandemic. This multicenter retrospective study investigated the still poorly understood impact of the COVID‐19 pandemic on colorectal cancer treatment in Japan. Methods This study was organized by the Clinical Study Group of Osaka University, which comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…In the present study, 11.3% fewer patients underwent surgery for CRC during the pandemic compared with in the pre-pandemic period. This is similar to the results of a previously reported cohort based in Japan [20,24]. In Japan, guidelines for performing surgical triage during the COVID-19 pandemic established by the Japanese Surgical Society (following the triage guidelines of the American Colleges of Surgeons) became widely used across the country [25,26].…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, 11.3% fewer patients underwent surgery for CRC during the pandemic compared with in the pre-pandemic period. This is similar to the results of a previously reported cohort based in Japan [20,24]. In Japan, guidelines for performing surgical triage during the COVID-19 pandemic established by the Japanese Surgical Society (following the triage guidelines of the American Colleges of Surgeons) became widely used across the country [25,26].…”
Section: Discussionsupporting
confidence: 84%
“…Similar ndings have been observed from other countries [15,21,22]. Miyo et al reported reductions in surgeries and colonoscopies of 10.4% and 14%, respectively, in Japan in their retrospective study [23]. Two other singlecenter studies in Korea showed 5.4% and 24.3% decreases in CRC patients between 2019 and 2021, respectively [24,25].…”
Section: Discussionsupporting
confidence: 81%
“…In Japan, colorectal cancer may have been diagnosed at a more advanced stage since the COVID‐19 pandemic 24,25 . In a cohort study in northern England, HCC tumor sizes were larger, and the incidence of spontaneous tumor bleeding was higher from March 2020 to February 2021 than from March 2019 to February 2020 26 .…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In a cohort study in northern England, HCC tumor sizes were larger, and the incidence of spontaneous tumor bleeding was higher from March 2020 to February 2021 than from March 2019 to February 2020.…”
mentioning
confidence: 99%